Liquid Chromatographic Analysis of α-Dicarbonyls Using Girard-T Reagent Derivatives - Lawrence, G.D. (Oxford University Press, 2017)
The measurement of a-dicarbonyls and other degradation products of sugars has become important in view of their toxicity. Although there are several methods used for their analysis, most require long reaction times to form UV absorbing or fluorescent derivatives and the nonpolar nature of commonly used derivatives necessitates relatively high concentrations of organic solvents for elution in reverse phase liquid chromatography. The present method describes the use of Girard-T reagent in a simple, one step derivatization of a-dicarbonyls and conjugated aldehydes and analysis using ion-pair reverse phase liquid chromatography. The limit of detection was in the range of 0.06-0.09 μM (4-12 ng/mL) for glyoxal, methylglyoxal, 3-deoxyglucosone and 5-hydroxymethylfurfural with good linear response and reproducibility using UV detection. The hydrazone derivatives were stable for several days in solution. The method was used to study degradation of several sugars and quantification of the target a-dicarbonyls and 5-hydroxymethylfurfural in several soft drinks. © The Author 2017.